Carinata Dry Matter Accumulation and Nutrient Uptake Responses to Nitrogen Fertilization. (1st July 2019) - Seepaul, Ramdeo; Marois, Jim; Small, Ian M.; George, Sheeja; Wright, David L.
Abstract : Core Ideas: This is the first report of carinata dry matter accumulation and allocation responses to nitrogen. Carinata growth, resource allocation, seed, and straw nitrogen concentration and uptake are highly responsive to nitrogen application in North Florida. Dry matter accumulation increases with nitrogen rate; however, the allocation of dry matter to roots, leaves, stems, flower/pods and seeds are similar regardless of nitrogen rate. Maximum nitrogen uptake occurred between 50% bolting and 50% flowering while all other elements had maximum uptake later in the season between 50% flowering and pod formation. Total nitrogen uptake exceeded applied N by 11 to 160%, suggesting that carinata is highly efficient at scavenging and utilizing residual soil nitrogen. Adequate nitrogen is required (93 kg N ha −1 ) for optimizing carinata productivity in sandy loam soils in North Florida. Brassica carinata is grown as a winter crop in the Southeast United States and it is a non‐edible oilseed feedstock for 'drop‐in' aviation and transportation fuels. The objective of this 2‐yr study was to determine the effects of N application on dry matter (DM) production and the accumulation of nutrients in above‐ and belowground biomass. Carinata var. 110994EM was treated with four N rates (0, 45, 90, and 135 kg N ha −1 ) in 2014 and 2015 at Quincy, Florida. Above‐ and belowground biomass were collected and analyzed for macro‐ and micronutrients. The allocation of DM among root, leaves, stems, flowers/pods, and seed did not differ with N rate. Carinata was highly responsive to N with maximum yield (2798 kg ha −1 ) produced at 102.3 kg N ha −1, while the economic optimum N rate occurred at 93 kg N ha −1 . Maximum N uptake occurred between 50% bolting and 50% flowering while all other elements had maximum uptake between 50% flowering and pod formation. Nitrogen concentration in seed and straw increased with N rate. These results were attributed to the strong relationship between uptake and dry matter production. Total N uptake exceeded applied N by 11 to 160%, suggesting that carinata is highly efficient at scavenging and utilizing residual soil N. The identification of growth stages associated with maximum nutrient uptake may aid in aligning time of N application to critical growth stages corresponding to maximum N uptake.